Early life socioeconomic circumstance and late life brain hyperintensities--a population based cohort study. - Alison D Murray (Public Library of Science (PLoS), 2014)
Context There have been many reports confirming the association between lower childhood socioeconomic circumstance and cardiovascular disease but evidence for links with cerebrovascular disease is contradictory. Hyperintensities on brain magnetic resonance imaging are associated with vascular risk factors, cognitive decline, dementia and death. However, the relationship between childhood socioeconomic circumstance and these lesions is unclear. Objective To test the hypothesis that childhood socioeconomic circumstance is associated with late life hyperintensity burden and that neither adult socioeconomic circumstance nor change in socioeconomic circumstance during life influence this effect. Design Cohort study. Setting Community. Participants 227 community dwelling members of the 1936 Aberdeen Birth Cohort aged 68 years, who were free from dementia. Main outcome measures Relationship between early life socioeconomic circumstance (paternal occupation) and abundance of late life brain hyperintensities. Results We find significant negative correlations between childhood socioeconomic circumstance and white matter hyperintensities (ρ = -0.18, P<0.01), and periventricular hyperintensities (ρ = -0.15, P<0.05), between educational attainment and white matter hyperintensities (ρ = -0.15, P<0.05) and periventricular hyperintensities (ρ = -0.17, P<0.05), and between childhood intelligence and periventricular hyperintensities (ρ = -0.14, P<0.05). The relationship is strongest for childhood socioeconomic circumstance and regional white matter hyperintensities, where there is a step change in increased burden from paternal occupation grades equivalent to a shift from "white collar" to "blue collar" paternal occupation. Significant correlations were also found between hypertension and hyperintensity burden in all brain regions (ρ = 0.15-0.24, P<0.05). In models that include hypertension, the magnitude of the effect of childhood socioeconomic circumstance is similar to and independent from that of hypertension. Conclusions Childhood socioeconomic circumstance predicts the burden of brain white matter hyperintensities aged 68 years. The mechanism underlying this effect is unknown, but may act through fetal and/or early life programming of cerebrovascular disease. Future work to understand this vulnerability will inform strategies to reduce dementia and stroke.